Burnout in Health Care Providers (Journal of Organizational Psychology, 2020)
Many factors have been linked to burnout, such as demonstrating a lack of resiliency, being over worked, and under poor leadership. Social constructs, such as inter-professional collaboration, may impact the experience of burnout. This study fills a gap in the organizational psychology literature regarding methods of preventing burnout, considering these methods in relation to gender, ethnicity, health-training status, and years in service. Eighty-seven people from three categories of health-training status were surveyed using the Inter-professional Collaboration Scale and Maslach Burnout Inventory. Multiple regressions were computed to predict burnout. Findings are discussed in the context of relevant theories.
Keywords: Organizational Psychology; burnout; physicians; nurses; inter-professional collaboration; career longevity; resiliency; ethnicity